Flexible, tough and high-performing ionogels for supercapacitor application - Paulina Pietrzyk-Thel; Amrita Jain; Kamil Bochenek; Monika Michalska; Michał Basista; Tamas Szabo; Peter B. Nagy; Anna Wolska; Marcin Klepka (Journal of Materiomics)
Ionogels are an attractive class of materials for smart and flexible electronics and are prepared from the combination of a polymer and ionic liquid which is entrapped in this matrix. Ionogels provide a continuous conductive phase with high thermal, mechanical, and chemical stability. However, because of the higher percentage of ionic liquids it is difficult to obtain an ionogel with high ionic conductivity and mechanical stability, which are very important from an application point of view. In this work, ionogel films with high flexibility, excellent ionic conductivity, and exceptional stability were prepared using polyvinyl alcohol as the host polymer matrix and 1-ethyl-3-methylimidazolium hydrogen sulfate as the ionic liquid using water as the solvent for energy storage application. The prepared ionogel films exhibited good mechanical stability along with sustaining strain of more than 100% at room temperature and low temperature, the ability to withstand twisting up to 360° and different bending conditions, and excellent ionic conductivity of 5.12 × 10−3 S/cm. The supercapacitor cell fabricated using the optimized ionogel film showed a capacitance of 39.9 F/g with an energy and power densities of 5.5 W⋅h/kg and 0.3 kW/kg, respectively confirming the suitability of ionogels for supercapacitor application.